Dynamics of multiple sustainable agricultural intensification practices adoption: Application of the intertemporal multivariate probit model - Ali Mohammed Oumer; Michael Burton; Menale Kassie (PLoS ONE, 2025)
Applying an intertemporal multivariate probit model, we reveal complex complementarity and substitution effects as well as new insights on the drivers of adopting input-intensive and natural resource management (NRM) practices in rural Ethiopia. First, the latent factor that drives each practice is positively and significantly correlated across time, suggesting persistency in adoption decisions. Second, the significant synergies and tradeoffs between the input-intensive and NRM practices underscore that these practices are highly compatible and, hence the importance of promoting technology packages. Third, the covariates that drive adoption significantly differ between practices, reflecting the heterogeneity in farmer behavior. Farm size was associated with the adoption of several input-intensive and NRM practices while off-farm income has the reverse effect. These findings have significant implications for food security policy in sub-Saharan Africa.